Computed Tomography analysis of damage in composites subjected to impact loading (Fracture and Structural Integrity, 2013)
The composites, used in the transportation engineering, include different classes with a wide range of materials and properties within each type. The following different typologies of composites have been investigated: laminated composites, PVC foam sandwiches, aluminium foam and honeycomb sandwiches. Aim of this paper was the analysis of low-velocity impact response of such composites and the investigation of their collapse modes. Low velocity impact tests were carried out by a drop test machine in order to investigate and compare their structural response in terms of energy absorption capacity. The failure mode and the internal damage of the impacted composites have been, also, investigated using 3D Computed Tomography.